2012
DOI: 10.1200/jco.2011.39.7505
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, Metformin, and Breast Cancer in Postmenopausal Women

Abstract: Metformin use in postmenopausal women with diabetes was associated with lower incidence of invasive breast cancer. These results can inform future studies evaluating metformin use in breast cancer management and prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
142
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(147 citation statements)
references
References 53 publications
4
142
1
Order By: Relevance
“…A smaller study of 90 women with diabetes and breast cancer reported an increased frequency of progesterone receptor-positive breast tumours among metformin users 16 . Finally, a study from the U.S. Women's Health Initiative found that metformin users were less likely to present with invasive breast cancer; however, the authors did not explore the relationship between metformin and breast cancer stage 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A smaller study of 90 women with diabetes and breast cancer reported an increased frequency of progesterone receptor-positive breast tumours among metformin users 16 . Finally, a study from the U.S. Women's Health Initiative found that metformin users were less likely to present with invasive breast cancer; however, the authors did not explore the relationship between metformin and breast cancer stage 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Whether metformin affects molecular breast cancer subtype is controversial. One study reported a reduction in hormone-sensitive tumours with metformin exposure 15 ; others reported either an increase 16,17 or no difference in hormone-positive tumours 14 . Those prior studies have been limited by small sample sizes, incomplete drug data, and inconsistent comparator groups and statistical methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some pharmacoepidemiologic studies have suggested that metformin may have antineoplastic activity (21)(22)(23)(24)(25)(26)(27) but others have not supported this view (28)(29)(30)(31). Similarly, some (10) but not all (32) laboratory studies suggest that metformin has antineoplastic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging data suggest that metformin treatment is associated with reduced breast cancer incidence and mortality for individuals with type II diabetes [7,6,17]. For years, many studies have been done to investigate the possible direct and indirect effects of metformin on cancers of various origins.…”
Section: Diabetes Breast Cancer and Metforminmentioning
confidence: 99%